Effort estimation model for software development projects based on use case reuse. Issue 2 (31st October 2018) - Rak, Katija; Car, Željka; Lovrek, Ignac
Abstract: This paper describes a new effort estimation model based on use case reuse, called the use case reusability (UCR), intended for the projects that are reusing artifacts previously developed in past projects with similar scope. Analysis of the widely spread effort estimation techniques for software development projects shows that these techniques were primarily intended for the development of new software solutions. The baseline for the new effort estimation model is the use case points model. The UCR model introduces new classification of use cases based on their reusability, and it includes only those technical and environmental factors that according to the effort estimation experts have significant impact on effort for the target projects. This paper also presents a study which validates the usage of UCR model. The study is conducted within industry and academic environments using industry project teams and postgraduate students as subjects. The analysis results show that UCR model can be applied in different project environments and that according to the observed mean magnitude relative error, it produced very promising effort estimates. Abstract : This paper describes a new effort estimation model based on use case reuse, called the use case reusability (UCR), intended for the projects that are reusing artifacts previously developed in past projects with similar scope. The baseline for the new effort estimation model is the use case points model. The UCR model introduces new classification of use cases based on their reusability, and it includes only those technical and environmental factors that according to the effort estimation experts have significant impact on effort for the target projects.